GeoGebra Landscape Research in Mathematics Learning - Ritmayanti, Indah Rahmania; Fitri, Rahmia Mulya; Dasari, Dadan; Samosir, Christina Monika; Marchy, Febrinna (Universitas Suryakancana, 2024)
GeoGebra is a software designed to facilitate the teaching and learning of mathematics, aiming to enhance students' comprehension of math concepts through its various digital tools and interactive features. The purpose of this study was to examine the research landscape related to the use of GeoGebra in the learning of mathematics. A descriptive bibliometric analysis method was used in this study. The data was retrieved from the Scopus database. According to the study, the number of publications related to GeoGebra in mathematics learning fluctuates annually. The year 2015 saw the highest number of citations compared to any other year. Turkey is the most influential country in this field. In the 2010–2015 and 2016–2020 ranges, the research focus was almost the same, or in other words, there were no significant differences in keywords. However, in the 2021–2023 range, the research focus has a renewal. Many new keywords have appeared.